2022
DOI: 10.30605/proximal.v5i2.1849
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Finger Math Method Menjadi Pinball Game Untuk Melatih Keterampilan Berhitung Perkalian Siswa Sekolah Dasar

Tasia Puspita Sari

Abstract: Each student has a different level of understanding, the teacher does not use enough teaching aids, which makes learning very everyday and monotonous or uninteresting. And the teacher does not use counting methods to help students understand, so students have a heavy memory load, such as remembering. multiplication. So the researchers developed the Jarimatika method into a pinball game to help determine the multiplication questions from 6 to 15 and design the visualization to make it more interesting. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results of research conducted by Ksatriani (2018) showed that the pinball game could increase motivation by 10.8% from 75.11% to 85.19%, with a gain score reaching 0.4%, which is in the medium category (Ksatriani, 2018). Learning math counting skills using pinball games is proven to improve math skills by more than 80% (Sari, 2022). Therefore, in this study, we developed posters combined with pinball games to invite COVID-19 vaccinations for elementary school children and their parents.…”
Section: Design Stagementioning
confidence: 99%
“…The results of research conducted by Ksatriani (2018) showed that the pinball game could increase motivation by 10.8% from 75.11% to 85.19%, with a gain score reaching 0.4%, which is in the medium category (Ksatriani, 2018). Learning math counting skills using pinball games is proven to improve math skills by more than 80% (Sari, 2022). Therefore, in this study, we developed posters combined with pinball games to invite COVID-19 vaccinations for elementary school children and their parents.…”
Section: Design Stagementioning
confidence: 99%